Review on the bond behavior and durability of FRP bars to concrete - Nepomuceno, Eduarda (2021)
In the past two decades, the use of Fiber Reinforced Polymer (FRP) bars in reinforced concrete structures has been increasing, replacing conventional steel reinforcement, especially in areas with adverse environmental conditions. This paper presents a literature review on the bond behavior of FRP bars to concrete, which includes studies on their (i) instantaneous and (ii) long-term (durability) properties. This work also included a database created from the collection of experimental data in the existing literature, with results from a total of 1002 pullout tests, intended to clarify the most relevant parameters that influence the bond of FRP bar to concrete. The analysis conducted on the database yielded the conclusion that FRP bar exhibits a good performance as reinforcement in concrete structures. Moreover, the collected data allowed the development of FRP bar to concrete bond (durability) long-term predictions considering the type of exposure environment.